Do Restoring and Maintaining Sinus Rhythm Have a Beneficial Effect on Secondary Prevention of Stroke in Patients With Atrial Fibrillation? A Pilot Study. (November 2019) - Conkbayir, Cenk; Yigit, Zerrin; Hural, Refika; Ugurlucan, Murat; Oztas, Didem Melis; Okcun, Baris; Kucukoglu, Serdar
We aimed to determine whether attempts to restore and maintain sinus rhythm will reduce recurrent stroke in patients with atrial fibrillation (AF). Patients (n = 245) between March 1998 and May 2002 with AF who had an ischemic stroke including transient ischemic attack 1 to 12 months before transesophageal echocardiographic examination and had been followed for 3 years were retrospectively reviewed. Cardioversion was attempted in 130 patients; 117 (90%) patients were successfully cardioverted (rhythm control group). The 13 patients who could not be cardioverted and 115 patients who did not undergo cardioversion were assigned to the rate control group. Age, gender, ischemic heart disease, hypertension, diabetes mellitus, congestive heart failure, mitral valve disease, and left atrial diameter were similar in both groups. The rhythm control group included 56 patients (48.7%) who were still in sinus rhythm after 3 years. During follow-up, there were 2 embolic events (3.4%) and 2 deaths (3.4%) in the rhythm control group, whereas 18 embolic events (14.6%) and 18 deaths (14.6%) occurred in the rate control group ( P = .049 and P = .049, respectively). Restoration and maintenance of sinus rhythm seems to have a beneficial effect on secondary prevention of stroke in patients with AF.